N-(4-Chlorophenylsulfonyl)-2-methylpropanamide - Nirmala, P. G. (International Union of Crystallography, 2011)
In the crystal structure of the title compound, C(10)H(12)ClNO(3)S, the N—C bond in the C—SO(2)—NH—C segment has a gauche torsion with respect to the S=O bonds. The molecule is twisted at the S atom with a C—S—N—C torsion angle of −62.3 (3)°. The benzene ring and the SO(2)—NH—CO—C segment form a dihedral angle of 89.3 (1)°. In the crystal, molecules are linked by pairs of N—H⋯O hydrogen bonds into inversion dimers.